Vector-borne alpha virus infections - Weaver, Scott (Henry Stewart Talks, 2010)
Overview of the alphaviruses, Systematics and evolution, Structure and replication, Disease and pathogenesis, Diagnosis, control and prevention of disease, Update interview: Newly discovered alphaviruses, Update interview: Continued chikungunya emergence and global spread, Update interview: Variation in chikungunya virus virulence and transmission, Update interview: Mayaro virus, Update interview: Lack of recent (since 1995) epizootic Venezuelan equine encephalitis, Update interview: Increase in eastern equine encephalitis, Update interview: Discontinuation of commercial Ross River vaccine development, Update interview: New strategies to control mosquito vectors such as Aedes aegypti, Update interview: Alphavirus emergence and spread based on founder effects: chikungunya findings, Update interview: Alphavirus vaccine development
Updated at 2021/03/03